Assisted Reproductive Technology Outcomes in Women With Heart Disease - Quien, Mary M.; Hausvater, Anaïs; Maxwell, Susan M.; Weinberg, Catherine R. (Frontiers in Cardiovascular Medicine, 2022)
Background Women with infertility and heart disease (HD) are increasingly seeking assisted reproductive technology (ART). There is only one other study that examines the safety profile of ART in this population. This study aims to evaluate the cardiac, reproductive, and obstetric outcomes of ART in women with HD. Methods We conducted a retrospective case-control study of women with underlying congenital or acquired HD who underwent ART at a single university fertility center from 1/2010-3/2019. Women undergoing in-vitro fertilization (IVF), oocyte cryopreservation (OC) or embryo banking (EB) with HD were included. Cases were matched 3:1 with age-, cycle type- and cycle start date- matched controls without HD. Outcomes included cardiovascular (CV), reproductive, and obstetric complications during or following ART. Results 20 women with HD were included. 15 (75%) had congenital HD, 1 (5%) had valvular disease, 1 (5%) had acquired cardiomyopathy, and 3 (15%) had arrhythmias. 90% were New York Heart Association class I. 55% of HD cases were modified WHO (mWHO) risk classification 1-2, 40% were mWHO 2-3 or 3, 5% were mWHO 4. Cases underwent 25 IVF, 5 OC, and 5 EB cycles and were compared with 79 controls who underwent 174 cycles. No CV complications or deaths occurred amongst cases following ART or pregnancy. There was no difference in risk of ART or obstetric outcomes amongst cases versus controls. Conclusion For women with HD in this small, low -risk cohort, ART posed few risks that were similar in frequency to healthy controls.